Cognitive and symbolic meaning of the «black» color in a literary text - Bezaubekova, А.Д.; Kanapina, С.Ғ.; Esirkepova, К.Қ. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The article examines the ways of transmitting the "black" color in a symbolic sense in the work of the writer T. Akhtanov, "The Light of the hearth" and the skill of its use. Through the use of the word by the writer in symbolic expression, the worldview, culture, and artistic world of the author are known in increasing the figurativeness of the work. The linguistic personality of the characters is considered as a result of their cognitive activity, their linguistic and cognitive level. At the same time, the work establishes that the word blackness, by virtue of the phrase, means sadness, death, evil, vice, and then the word blackness indicates holiness, sacredness, and simplicity. Having comprehensively examined the ethnolinguistic character of the "black" color, it turns out that this is one of the most frequently used names in the Kazakh language, rich in meaning, with a wide range of applications. In the author's work, a large number of black names were noticed, used in the meaning of "sacred", "holy".